'If they do not want to work and suffer, they must starve and die.'Irish and Finnish famine historiography compared. Issue 4 (8th August 2018) - Forsberg, Henrik Mikael
Abstract : The 19th century is often depicted as an age of great transformations: industrialism, nation-building and economic progress. Likewise, it is also the period when Europe was struck by the last great famines during peace-time. In this article, I will, first, give a short presentation of how the famines in Finland in 1866–1868 and Ireland in 1845–1852 unfolded and, second, offer some insights into the similarities between these famines, especially with respect to the relief policies adopted by authorities. Finally, the article will focus on how the question of food exports and imports acquired markedly different historiographical meanings. Comparative historiography, especially when applied to famine historiography, provides a hitherto neglected resource that can shed light on how national histories are written and interpreted and the extent to which they might reflect a truly essential peculiarity about the societies in question.